The responsibilities of the state and businesses in the creation of social capital - Mateusz Kurowski (Economic and Environmental Studies (E&ES), 2016)
According to different types of studies conducted in recent years, not natural but social factors will constitute a major barrier in the process of achieving sustainable development. The barrier will be quickly noticed in the countries and regions of low social capital. The purpose of this article is to present responsibilities for state authorities and enterprises in the creation of social capital. This conducted study of literature has enabled the creation of a set of methods that impact these entities as to the nature of the relationship and level of trust within certain social structures. This presented work may serve as reference points for entities implementing similar solutions in their environment. The author cites numerous examples which oppose the opinion that the level of social capital is only a result of inheritance. The current generation can take the initiative in this regard, although it is a long-term process. The author also points out the dependence of the effectiveness of measures taken to adapting them to the specific context in which the group operates. He also draws attention to the role of society, which, like the state and commercial entities is responsible for raising the level of social capital.
Keywords: Z13; M14; 330; social capital; sustainable development; corporate social responsibility; CSR